HERITAGE, PHOTOGRAPHY AND THE AFFECTIVE PAST. - STERLING, COLIN.
1 online resource (1 volume)
Keywords: Heritage, Photography, and the Affective Pastcritically examines the production, consumption, and interpretation of photography across various heritage domains, from global image archives to the domestic arena of the family album. Through original ethnographic and archival research, the book sheds new light on the role photography has played in the emergence, expansion, and articulation of heritage in diverse sociocultural contexts. Drawing on wide-ranging experience across the heritage sector and two international case studies - Angkor in Cambodia and the town of Famagusta, Cyprus -the book makes a major contribution to our understanding of the role photography has played and continues to play in shaping experiences and conceptualisations of heritage. One of the core aims of the book is to problematise and potentially redirect the varied usages of photography within current practice, usages which remain woefully undertheorised, despite their often-central role in shaping heritage. Ultimately, by focusing attention on a hitherto underexamined aspect of the heritage phenomenon, namely its manifold interconnections with photography, this book provides fresh insightto the making and remaking of the past in the present, and the alternative heritages that might come into being around emergent photographic forms and approaches. Heritage, Photography, and the Affective Past uses photography as a method of enquiry as well as a tool of documentation. It will be of interest to scholars and students of heritage, photography, anthropology, museology, public archaeology, and tourism. The book will also be a valuable resource for heritage practitioners working around the globe.